Fish Farmers’ Information Needs: Implications for Fisheries Extension - Salas, Shalumol; Ojha, S. N.; Vipinkumar, V. P.; Dona, P. (Fishery Technology, 2019)
The farming community requires an offset of variedinformation for their day to day agriculturalactivities. Assessing farmers information needs is animportant aspect of any endeavour aimed toenhance the availability of, and access to informationamong farmers. The study investigated theinformation needs of farmers engaged in fishfarming in Alappuzha district, Kerala State. A wellstructuredand pre-tested interview schedule wasused to collect information from sixty randomlyselected fish farmers from two fish farmers’ agenciesin the area. The identified needs were ranked interms of weighted score. Information on extensionservice providers, emerged as the most neededinformation among the respondents. The recommendationsof the study are given for developingand implementing extension service and deliverymechanism with relevant modification and redesigningof available technologies and setting up ofawareness and capacity building programmes forfish farmers regarding aquaculture farm informationand related needs.